Galerie des Glaces sebagai Sumber Ide Penciptaan Busana Pesta - Wening, Praba Sari Kartika; Yulistiana, Yulistiana (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The Galerie des Glaces, a renowned hall in the Palace of Versailles,  is distinguished by its extensive glass panels and chandeliers, which occupy a dominant position within the space. The present article aims to explore the visual elements of the Galerie des Glaces, applying fabric manipulation techniques and defining fashion silhouettes. The text delves into the process of creating and finalizing a party dress inspired by this iconic space. The research method employed is the Double Diamond Model, which comprises four stages. discovery (the collection of information and the generation of ideas), define (the organization of the information into a moodboard), develop (the creation and refinement of designs based on the moodboard), and deliver (the evaluation of the prototype and the selected design). The findings of this study indicate that the Galerie des Glaces space, characterized by its architectural ornamentation, serves as a valuable source of inspiration for the design of party wear, particularly through the incorporation of elegant silhouettes, the manipulation of fabric cord, and the strategic placement of fringe. The resulting party wear designs were not only visually appealing, but also reflected elegance, resulting in exclusive and storytelling party wear.